PUPPET MOVEMENTS IN STRUCTURE-SPECIFIC TRADITIONAL PAPER CUT OUT ANIMATION PRODUCTION - Dominika Anggraeni Purwaningsih (ULTIMART Jurnal Komunikasi Visual, 2020)
Physical paper puppets are inanimate objects, but when we’re speaking in terms of the production of traditional paper cut out animation, they become the actors and the souls that drive the movie. When shooting and animating traditional paper cut out animation, the puppets are laid flat on a surface so they can only move in limited directions compared to conventional 2D or 3D animation. As we know, each character in animated movie has its own personality and unique to each other. The challenge lays in bringing out the characteristics and personality of the character through the limited medium of paper puppet. In this qualitative research, puppet movements will be applied to quadruped cat characters in a public service announcement titled “Spay & Neuter”. The puppet along with the visual design, segmentations, and joints were done in previous research. Qualitative observations and audio-visual materials are used to collect the data for references. Literature review will study the characteristics of cats, body language, behaviour, and principles of animation especially timing and exaggeration. Observation is conducted by studying the movements of real cats from online videos and direct observations and also studying how other animators animate cat characters in animated films. In the exploration stage, paper puppets will be animated according to the movement design while experimenting with the timing and frame rate of the stop motion to achieve the final results.